(untitled) (Global Journal of Science Frontier Research, 2023)
Quantum information technology mainly includes quantum communication quantum radar quantum computer these three aspects in recent years rapid development many countries invested heavily in development The awarding of the Nobel Prize in Physics in 2022 to three scientists for their work in quantum informatics has further stimulated people s interest in quantum theory which has been studied and discussed This paper not only reviews the historical situation but also thinks and innovates in theory The main contents of this paper are as follows It is pointed out that there are fundamental contradictions between relativity and quantum mechanics The wave function quantum statistics and uncertainty principle are discussed in detail The hidden variable theory is reviewed and the Bell inequality is discussed The Aspect two-photon experiment was analyzed The rationality of Bohm experiment scheme is discussed The development of Bell type experiment is discussed It is pointed out that the entangled state is not acting at a distance but propagating faster than the speed of light Reviews the Copenhagen interpretation of quantum mechanics Quantum communication and Wootters theorem are discussed etc This paper holds that quantum mechanics has been finalized from 1926 to 1928 and its basic content has not changed much But for some of the accusations it is necessary to answer them theoretically For example we believe that the Copenhagen interpretation fundamentally changes our understanding of nature and marks a profound revolution in physics And no other theory has since emerged that has such a profound understanding and wide application of microscopic phenomena as this interpretation Another example is Bohm s two-particle correlation spin scheme in quantum entanglement experiments which has been proved to be effective in a series of experiments which is an important contribution in Bohm s life This paper holds that the so-called quantum field theory is a failure and the original quantum mechanics should still be advocated today Current theoretical research should pay great attention to quantum entangled states because its nature is still unclear Understanding this first mystery of the physical world not only has scientific significance but also has great philosophical significance for understanding the universe